THE EFFECT OF WEBSITE QUALITY, E-TRUST, AND E-SERVICE QUALITY TO REPURCHASE INTENTION ON TRAVELOKA.COM USERS IN INDONESIA - Sakha Andhika; Naili Farida; Apriatni E Prihatini (Universitas Diponegoro, 2025)
Abstract: Online Travel Agent (OTA) is present as an embodiment of the development of information and communication technology. Traveloka.com as one of the OTA companies in Indonesia has been around since 2012 and has become the number one service company compared to other OTAs. This research was conducted to determine the influence of website quality, e-trust, and e-service quality on repurchase intention among Traveloka.com users in Indonesia. This research uses explanatory research type with a sample size of 150 respondents. Sampling used a non-probability sampling technique, namely purposive sampling. This research uses a quantitative approach using the SPSS for Windows version 25.0 application for data processing. The results of the research show that the variables Website Quality (X1), E-Trust (X2), and E-Service Quality (X3) have a positive and significant effect on the variable Repurchase Intention (Y) partially, as well as the variables Website Quality (X1), E-Trust (X2), and E-Service Quality (X3) simultaneously have a positive and significant effect on the Repurchase Intention (Y) variable. The variable with the largest contribution is Website Quality (X1) with a contribution percentage of 27.3%. Keywords: Website Quality; E-Trust; E-Service Quality; Repurchase Intention Abstraksi: Online Travel Agent (OTA) hadir sebagai perwujudan dari perkembangan teknologi informasi dan komunikasi. Traveloka.com sebagai salah satu perusahaan OTA di Indonesia telah hadir sejak tahun 2012 telah menjadi perusahaan jasa layanan nomor satu dibandingkan dengan OTA lainnya. Penelitian ini dilakukan untuk mengetahui pengaruh website quality, e-trust, dan e-service quality terhadap repurchase intention pada pengguna Traveloka.com di Indonesia. Penelitian ini menggunakan tipe explanatory research dengan jumlah sampel sebanyak 150 responden. Pengambilan sampel menggunakan teknik non-probability sampling, yaitu purposive sampling. Penelitian ini menggunakan pendekatan kuantitatif dengan menggunakan bantuan aplikasi SPSS for windows versi 25.0 untuk pengolahan data. Hasil penelitian menunjukkan variabel Website Quality (X1), E-Trust (X2), dan E-Service Quality (X3) berpengaruh positif dan signifikan terhadap variabel Repurchase Intention (Y) secara parsial, serta variabel Website Quality (X1), E-Trust (X2), dan E-Service Quality (X3) secara simultan berpengaruh positif dan signifikan terhadap variabel Repurchase Intention (Y). Variabel dengan kontribusi paling besar adalah Website Quality (X1) dengan persentase kontribusi sebesar 27,3%. Kata Kunci: Website Quality; E-Trust; E-Service Quality; Repurchase Intention